2011
DOI: 10.1080/00288330.2010.538067
|View full text |Cite
|
Sign up to set email alerts
|

Movement patterns of the East Coast rock lobster Panulirus homarus rubellus on the coast of KwaZulu-Natal, South Africa

Abstract: A tagging study was undertaken on Blood Reef off Durban, South Africa, to investigate movement patterns of Panulirus homarus rubellus as well as inshore/offshore population differences. Lobsters were collected by SCUBA divers and baited traps. Traps caught larger lobsters than divers and trap catches were somewhat male-dominated (40% female:60% male). Lobsters were predominately resident with only 3% of recaptured lobsters moving over 500 m. Long shore movements were probably related to foraging behaviour and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…This is unlikely, as previous studies of migration in the Panulirus species caught by this fishery have shown that only P. ornatus undertake substantial migrations (Bell et al, 1987;Fisch, 2007b;Steyn and Schleyer, 2011). These studies have shown that the other species of Panulirus lobsters may move locally, but that these movements are not predictable and do not appear to be in response to environmental stimuli.…”
Section: Environmental Influences On Catchmentioning
confidence: 69%
See 2 more Smart Citations
“…This is unlikely, as previous studies of migration in the Panulirus species caught by this fishery have shown that only P. ornatus undertake substantial migrations (Bell et al, 1987;Fisch, 2007b;Steyn and Schleyer, 2011). These studies have shown that the other species of Panulirus lobsters may move locally, but that these movements are not predictable and do not appear to be in response to environmental stimuli.…”
Section: Environmental Influences On Catchmentioning
confidence: 69%
“…This pattern is consistent with the fishers' hypothesis that a sharp increase in rainfall at the commencement of the wet season increased turbidity and made the lobsters, especially P. penicillatus, more active. Most P. penicillatus occupy inshore rocky reefs in shallow water ( o10 m) where wave action ensures that the water turbidity would be consistently higher than found on the deeper, offshore reefs where P. homarus live (Steyn and Schleyer, 2011). The much stronger relationship between catch rates and total catch compared with fishing effort also suggests that there is a seasonal increase in catchability that fishers have learnt to exploit by increasing fishing effort (Fig.…”
Section: Environmental Influences On Catchmentioning
confidence: 85%
See 1 more Smart Citation
“…Studies of foraging behavior of spiny lobsters from California (Withy-Allen & Hovel 2013) as well as other palinurids (Green et al 2013, Steyn & Schleyer 2011 suggest that lobsters are relatively mobile, moving hundreds of meters per night as they forage for food. However, these studies also show that spiny lobsters have high site fidelity and generally stay within a 1 ha area for weeks to months.…”
Section: Discussionmentioning
confidence: 99%
“…Of those species, P. penicillatus and P. homarus are the prevalent species caught by fishermen (Aisha and Triharyuni 2010). Most of P. penicillatus lives inshore rocky reefs in shallow water (< 10 m) than offshore because water turbidity would be consistently higher than that on the deeper (Steyn and Schleyer 2011).…”
Section: Introductionmentioning
confidence: 99%